Badania monitoringowe gleb na terenie Zakładu Unieszkodliwiania Odpadów w Ścinawce Dolnej w świetle przepisów prawnych wynikających z implementacji dyrektywy IED = Monitoring studies of soils in the disposal works in Ścinawka Dolna in the light of law resulting from the implementation of IED directive - Cuske, Mateusz; Szałata, Łukasz; Godzwa, Adam; Musztyfaga, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the basic characteristics of the physico-chemical properties and soil pollution in the disposal works in Ścinawka Dolna. This analysis is made in connection with the amendment of the environmental legislation in Poland takes into account the guidelines for the development of the basic report for IPPC installations.
Keywords: instalacja IPPC; dyrektywa IED; raport początkowy; IPPC installation; IED Directive; basic report